Social Management: Epistemology Beyond Paradigms - Silva Oliveira, Daniel José (Organizações & Sociedade, 2021)
The objective of this theoretical essay is to propose a new path for the epistemological debate in the field of social management that goes beyond the paradigmatic boundaries. Based on studies that deal with social management from different perspectives, a comparison was made between models based on the thesis of incommensurability by Thomas Kuhn – such as the Gibson Burrell and Gareth Morgan diagram of sociological paradigms – and an alternative to break away from the paradigmatic mentality: the circle of epistemic matrices. The study demonstrated that the logic of incommensurable paradigms is not adequate to guide social management studies due to its complexity and plurality. This was proven by the identification of multiple sociological approaches adopted in field studies, including hybrid approaches. In this sense, the circle of epistemic matrices proved to be more appropriate, because instead of impenetrable boundaries, it allows transit between the matrices and enables a dialogue between different sociological approaches.